Semiperfect ipri-rings and right Bézout rings - Gubareni, N. M.; Dokuchaev, M. A.; Kirichenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present a survey of some results on ipri-rings and right Bézout rings. All these rings are generalizations of principal ideal rings. From the general point of view, decomposition theorems are proved for semiperfect ipri-rings and right Bézout rings.